Fiber-coupled Al2O3:C radioluminescence dosimetry for total body irradiations. (October 2016) - Buranurak, S.; Andersen, C.E.
Abstract: In vivo dosimetry can be important and relevant in radiotherapy, especially when commissioning new treatment techniques at hospitals. This study investigates the potential use of fiber-coupled radioluminescence (RL) dosimetry based on Al2 O3 :C or organic plastic scintillators for this purpose in the context of Total Body Irradiations (TBIs) where patients are treated with large fields of 6 or 18 MV photons at an extended source-to-surface distance (SSD). The study shows that Al2 O3 :C dosimetry using the saturated-RL protocol may be suitable for real-time in vivo dosimetry during TBI treatments from the perspective of the good agreement with alanine dosimetry and other critical phantom tests, including the ability to cope with the large stem signal experienced during TBI treatments at extended SSD. In contrast, the chromatic stem removal technique often used for organic plastic scintillators did not work well in large fields with the tested calibration procedure and instrumentation. An apparent dose-rate effect discussed in a previous study of the RL properties of Al2 O3 :C (Andersen et al., 2011) was found to have resulted from an overlooked dead time problem in the counting system, and this potential caveat can therefore be removed from the list of potential problems associated with fiber-coupled Al2 O3 :C dosimetry using the saturated-RL protocol. This further has implications for TBI dosimetry using the RL Al2 O3 :C system due to large dose-rate differences between calibrations at the iso-center and in vivo measurements at extended source-to-surface distances. Highlights: Fiber-coupled dosimetry can be used for measurements during total body irradiations. An apparent dose-effect associated with radioluminescence from Al2O3:C was resolved. The gated-counting stem removal procedure worked well for Al2O3:C in pulsed accelerator beams. The chromatic stem removal procedure did not work well with the tested instrumentation and organic plastic scintillators.